PENGARUH PENILAIAN PRESTASI KERJA TERHADAP PENGEMBANGAN KARIR PEGAWAI - Ali Baba (AkMen JURNAL ILMIAH, 2014)
This study aims to determine the effect of performance appraisal of the employees in the development of PT Bank BRI Gowa. The research method is a survey. The population in this study were all employees at PT Bank BRI Gowa, amounting to 32 people .. Because the population of a small, sampling is 100 percent (saturated sample), the entire population as well as serve as sampel.Teknik collecting data through questionnaires, interviews , and as supporting documentation. Data analysis technique is a simple linear regression to determine the effect of independent variables on the dependent variable. The results showed that the performance appraisal and career development of employees at PT Bank BRI Gowa strongly correlate. This is indicated by the coefficient of determination (R2) of 0.964 (96.4 percent), while the results of the regression analysis showed a positive and significant effect.